Configuración del proceso de ventas y el módulo de contabilidad financiera sobre SAP S/4 Hanna (2021)
The use of personal computers in the work environment in the 80's, led to the information systems having a very limited scope and with very specific purposes. This led to the implementation of different systems in different areas of the company and, consequently, duplicity of data in these areas. In the 90's, companies began to implement enterprise systems (ES) whose objective is to integrate information across the company in a single system that supports their needs. One of the most widely used ES in the industry today is the Enterprise Resource Planning (ERP) system, and one of the leading companies in the ERP market is SAP. Their products have a considerable and complex implementation process. Therefore, this project aims to document the ERP S/4 Hana configuration for the sales process. The objective is to identify strengths and weaknesses of this ERP as it relates to its adaptation to a specific fictitious organization in the manufacturing sector, namely Global Bike Incorporated.